2003
DOI: 10.1017/s0022112002003579
|View full text |Cite
|
Sign up to set email alerts
|

Decaying turbulence in an active-grid-generated flow and comparisons with large-eddy simulation

Abstract: Measurements of nearly isotropic turbulence downstream of an active grid in the Corrsin wind tunnel are performed as a high-Reynolds number (Re λ ≈ 720) update of the Comte-Bellot & Corrsin (1971) data set. Energy spectra at four downstream distances from the grid, ranging from x/M = 20 to x/M = 48, are measured and documented for subsequent initialization of, and comparison with, Large Eddy Simulations (LES). Data are recorded using an array of four X-wire probes which enables measurement of filtered velociti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

34
244
2
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(285 citation statements)
references
References 33 publications
34
244
2
5
Order By: Relevance
“…In subsequent work he stresses that for constant ν (and η), only the case α = 1 can be realized. For nonhelical MHD, this is indeed compatible with simulations [23][24][25], but not for HD [26] nor for helical MHD [3,18]. In this Letter, we argue that the scaling exponent q is not primarily determined by the initial value of α, as suggested by Eq.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…In subsequent work he stresses that for constant ν (and η), only the case α = 1 can be realized. For nonhelical MHD, this is indeed compatible with simulations [23][24][25], but not for HD [26] nor for helical MHD [3,18]. In this Letter, we argue that the scaling exponent q is not primarily determined by the initial value of α, as suggested by Eq.…”
supporting
confidence: 76%
“…This decay behavior departs from what would be expected if the Loitsiansky integral were conserved, i.e., q = 2/7 and β = 4. A slower decay law with p = 6/5, corresponding to q = 2/5 and β = 2 has been favored by Saffman [29], while experiments and simulations suggest p = 5/4 [26,30].…”
mentioning
confidence: 99%
“…They found that both the velocity and temperature fluctuations decayed at similar rates. More recently, Kang et al (2003) performed an update of the Comte-Bellot and Corrsin (1971) dataset at a higher Reynolds number and compared it with LES using different subgrid-scale models.…”
Section: Introductionmentioning
confidence: 99%
“…However, various studies have already documented some limitations of LES results, for example when considering structure functions and space-time correlations (Kang, Chester & Meneveau 2003;Yang, He & Wang 2008). Matching some lower-order statistics is thus no guarantee that all other statistics are also accurately simulated.…”
Section: Futurementioning
confidence: 99%